Labour resources of «Physical culture and sport» branch - Хомко, І.; Лугова, А. (Slobozhanskyi Herald of Science and Sport, 2011)
In theses, the results of literary sources are described related to the problem of skilled potential of industry of physical culture and sport. The basic stages of management labour resources are described in organizations of athletic-sporting orientation in Ukraine.